(untitled) (Research, Society and Development, 2021)
Introduction: this is a form of diabetes in which autoimmunity against pancreatic beta cells develops more slowly and the mandatory use of insulin may occur after several diagnoses. In LADA, β-cell dysfunction has been reported as intermediate between the two main types of diabetes mellitus. Objective: to demonstrate answering the pathophysiology, diagnostic criteria of LADA and its association with autoimmune diseases. Methodology: this is a descriptive research of the integrative literature review type. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services databases. Results and discussion: because it is latent and slowly progressive, the diagnostic criteria for LADA are still very confusing, leading to a high rate of misdiagnosis. There is evidence in autoimmune diabetes for a continuum of genetic susceptibility, which extends from a marked effect in childhood-onset type 1 diabetes to the relatively limited effect detected in LADA. The diagnosis of LADA is currently based on three criteria: adult age at onset of diabetes, the presence of circulating islet autoantibodies; and lack of need for insulin for at least 6 months after diagnosis. Conclusion: Diagnosing autoimmune diabetes in individuals wrongly classified as type 2 is important, as it alerts to a probable insulin deficiency, avoiding delays in insulin therapy.